Durable pulmonary vein (PV) isolation at repeat atrial fibrillation (AF) ablation procedure: a comparison between 4 ablation technologies. (25th November 2020) - Morales, G; Boghossian, E; Rajendra, A; Osorio, J
Abstract: Background: Durable PV isolation is the sought-after endpoint to obtain long term success after AF catheter ablation. Evolution in technology improves efficiency, safety and effectiveness in AF catheter ablation. Purpose: To investigate the effectiveness of different catheter technologies in obtaining durable PV isolation in a real-world practice. Methods: Retrospective analysis of prospectively collected data of patients undergoing repeat procedures for recurrence of AF or atrial flutter at our institution was performed. Incidence of all PVs being isolated at repeat procedure was recorded and patients 4 groups created based on catheter technology used during index AF ablation procedure (SF: multipored, irrigated catheter; ST: contact force sensor catheter; Cryo: 2nd generation cryobaloon; and STSF: multipored, irrigated, contact force sensing catheter). Results: We identified 269 subjects undergoing repeat ablation from May 2014 to September 2019. Mean age was 67±9.7 years, 54.6% were males, 74.4% non-paroxysmal AF at the index procedure. The mean CHA2DS2Vasc score was 2.5±0.26, LA size 4.2±0.6 cm, EF 55.3±10%. The mean time from index to redo procedure was 374±331 days. At repeat procedure all veins were isolated in 24% (6/25) who were initially ablated using SF; 36% (8/22) with Cryo; 44% (47/108) with ST; and 74% (84/114) with STSF catheter. (Figure) Conclusion: Patients undergoing index ablation with STSF catheter technology were significantly more likely to have all 4 PVs isolated at repeat procedure compared to previous generation technology. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Biosense Webster